2019
DOI: 10.1049/iet-epa.2018.5803
|View full text |Cite
|
Sign up to set email alerts
|

Application of the inductive high current testing transformer for supplying of the measuring circuit with distorted current

Abstract: The increasing number of non-linear loads and renewable energy sources causes a decrease in the power quality in the power networks. Therefore, tests of current transformers should be performed in similar conditions. This requires generation by a high current testing transformer of distorted currents that rms values are from a few hundred to several thousands of amperes with a given harmonics levels. However, its frequency band of operation is limited by inductances of its windings and connected load that resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Meanwhile, if the rated secondary current of the tested CT is equal to 1 A, the combined uncertainties type B are respectively equal to ±0.01%, The step-up current transformer was previously tested during transformation of the distorted currents. In the paper [25], it was demonstrated that it is capable of wideband operation and shows no resonance in the tested frequency range of higher harmonics up to 5 kHz. Equations (1) to (5) are further used to determine values of the current and phase error of the transformation of harmonics of the distorted current.…”
Section: Verification Of Determined Values Of Current and Phase Errormentioning
confidence: 99%
“…Meanwhile, if the rated secondary current of the tested CT is equal to 1 A, the combined uncertainties type B are respectively equal to ±0.01%, The step-up current transformer was previously tested during transformation of the distorted currents. In the paper [25], it was demonstrated that it is capable of wideband operation and shows no resonance in the tested frequency range of higher harmonics up to 5 kHz. Equations (1) to (5) are further used to determine values of the current and phase error of the transformation of harmonics of the distorted current.…”
Section: Verification Of Determined Values Of Current and Phase Errormentioning
confidence: 99%
“…The measuring circuit is supplied by the programmable power voltage source through the insulating transformer [33]. If required for testes rms value of the primary current exceeds 20 A application of the inductive high current testing transformer for supplying of the measuring circuit with distorted current is required [34]. The oscilloscope is used to determine the waveforms of the excitation current measured by the RD resistor and the secondary voltage measured by the differential connection of two voltage probes.…”
Section: Figure 1 the Measuring Circuit To Determine The Values Of Cmentioning
confidence: 99%
“…In the presented application, the tested wideband power source was used for generation of a distorted current for supplying the step-up current transformer required for testing the inductive current transformer's accuracy in transforming the harmonics [7,17]. Therefore, laboratory tests were performed in order to determine their frequency band of operation and the required rms values of the main and higher harmonics of the distorted output current of the step-up current transformer.…”
Section: Application Of Tested Wideband Power Sourcesmentioning
confidence: 99%
“…In Figure 9 the following new notations are used: L nf -compensation inductor for 50 Hz component; C C1 -compensation capacitors for 50 Hz component; C Ch -switchable capacitor for compensation of higher harmonics; CT-current transformer; and HCT-step-up current transformer. The frequency band of the HCT operation is reported in [17]. The transformation accuracy of the CT, similar to the one used in this measuring system, is analyzed in [7].…”
Section: Application Of Tested Wideband Power Sourcesmentioning
confidence: 99%
See 1 more Smart Citation